The parametric instability improvement of fully anisotropic composite plates with embedded shape memory alloy. (17th January 2020) - Yusof, Zarina; Rasid, Zainudin A; Hassan, Mohamad Zaki; Sapuan, SM; Sarip, Shamsul; Yahaya, Hafizal; Yakub, Fitri
The parametric resonance or instability challenge in designing laminated composite is crucial in areas such as aeronautical and marine where structures experience dynamic loading. Shape memory alloy (SMA), a type of smart material, has been used to improve the structural behaviours of composite plate using its well-known property of shape memory effect. It is also known that mechanical couplings that exist in unsymmetric composite can increase the instability of the composite. In this study, the SMA property has been exploited to generate recovery stress in the composite to improve its parametric instability problem. The unsymmetric composites were embedded with SMA fibres, and the formulation for the dynamic instability of this composites was developed using finite element method. The third-order shear deformation theory of composite was applied. The results were initially validated for the case of composite without SMA. Following that, the parametric instability behaviour of unsymmetric composites was studied under the effect of several parameters. It was found that the mechanical couplings that exist in the unsymmetric composite have increased the instability of the composite, but the presence of the SMA can significantly reduce this instability.